In Vitro Antimicrobial Effectiveness Tests Using Garlic (Allium sativum) against Salmonella enterica Subspecies enterica Serovar Enteritidis - Elena Circella; Gaia Casalino; Francesco D'Amico; Nicola Pugliese; Michela Maria Dimuccio; Antonio Camarda; Giancarlo Bozzo (MDPI AG, 2022)
In recent years, there has been a more prudent use of drugs on livestock farms and alternative products have been considered, with a view of reducing the risk of the onset of antibiotic resistance. Salmonella enterica subsp. enterica serovar Enteritidis (S. Enteritidis) may cause disease in poultry, and it is also responsible for human food poisoning. The aim of this study was to evaluate the efficacy of garlic against S. Enteritidis and to define its Minimal Inhibitory Concentration (MIC)90 and MIC50 values. The study was carried out in vitro, testing 26 S. Enteritidis strains identified in laying hens from various farms in Southern Italy. A preliminary efficacy trial was carried out on two strains, S. Enteritidis and Escherichia coli, using a garlic concentration of 10 mg/mL (1%). Later, 26 strains of S. Enteritidis at 106 Colony Forming Unit (CFU) and 104 CFU were tested with different concentrations of garlic, ranging from 10 mg/mL to 1 mg/mL. Based on the results, intermediate concentrations of garlic, from 5 mg/mL to 4 mg/mL and 4 mg/mL to 3 mg/mL, were used to test 106 CFU and 104 CFU, respectively. The data were statistically analyzed. The MIC90 was 4.75 mg/mL for strains tested at 106 CFU and 4 mg/mL for strains tested at 104 CFU. The results highlight garlic's potential to inhibit the growth of Salmonella enterica ser. Enteritidis in vitro. Efficacy was dependent on the microbial concentration used. In vivo efficacy trials will be crucial to confirm the efficacy of garlic against S. Enteritidis and to assess whether garlic can be used in poultry flocks to prevent the spread of the bacterium in the field.